Electrically responsive ZnO nanotubes for controlled release of biomolecules. (August 2017) - Lin, C.C.; Chen, Y.W.; Hsiao, C.S.; Chen, S.Y.
Abstract: We developed a novel electro-responsive drug delivery device by depositing fluorescein isothiocyanate (FITC)-loaded zinc oxide nanotubes (ZTs) onto indium tin oxide (ITO)/polyethylene terephthalate (PET) substrates (called FITC-ZTs-ITO/PET). With a large payload of FITC up to 0.98 mmol g −1, the FITC-ZTs simultaneously provide a burst-like FITC release and a repeated step-like release after application of an electrical field at specific resonant frequencies. Additionally, FITC-ZTs-ITO/PET is biocompatible with both HeLa and MRC5 cells for ZT concentrations below 50 μg/ml. These results demonstrate that FITC-ZTs-ITO/PET is a new platform that can provide local, on-demand electrically responsive drug release for biomedical applications.